A Development of E-learning-Based Pocket Books to Improve Students' Cognitive Ability - Nurul Hidayah; Dwi Swastanti Ridianingsih (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2022)
The aim of this study is to develop a set of pocket book teaching materials that can improve students' cognitive abilities in basic science concepts. This research is included in the type of research and development (Research and Development) using the Borg & Gall research and development model. Research and development is a process to develop a new product or improve an existing product that can be accounted for. The products developed in this research are pocket book teaching materials and poster learning media based on E-Learning in the basic science concepts course. The results of the study found that students' cognitive results were known to have difficulty in answering questions given by the teacher during the learning process, because students before learning did not read the pocket books that had been provided, so there was a lack of knowledge and insight in answering questions given by the lecturer